Experience Quality's Impact on Green Customer Satisfaction Mediated by Green Perceived Value in the Malang Ecotourism Landscape - Fadhila, Wildan; Putra, Ketut Candra Pangestu (International Journal of Green Tourism Research and Applications, 2024)
This research, conducted using a quantitative-explanatory approach, aims to analyze the relationship between experience quality and customer green satisfaction, focusing on environmentally friendly tourist destinations in Malang City. The study collected data from 360 respondents through an online questionnaire and applied SEM-PLS for analysis. The respondents were selected purposively. The findings, which are of significant importance, indicate that experience quality significantly influences both customer green satisfaction and green perceived value, with the latter mediating the relationship between experience quality and customer green satisfaction. This reiteration of the findings underscores the importance of positive experiences and perceived environmental values in enhancing overall satisfaction at eco-friendly tourist destinations.